Med Kvinderne til velfærdsstaten - Kvindeorganisering i Danmark 1920-1940 - Hilda Rømer Christensen (The Royal Danish Library, 1999)
The article deals with womens organized contribution to the making of the Danish Welfare State during the interwar period. It is argued that women contributed substantially to the debate and the level of decision making. Women's contributions are traced both at the local and at the national levels and documentation derives from a wide range of associations: From conservative, religious ones such at the YWCA to the radical: The Working Women's Association. In the absence of a strong Social-Democratic women's association, the womens rights movement, The Danish Women's Society, became the nexus for a strong coalition of elite women, a networking female elite, with different political backgrounds. They consolidated a longstanding pattern for cooperation among organized women, which also remained in the period after 1945. The stress in this women's rights community was laid in equality measures, which constituted women as individuals with equal rights rather than as gendered persons and in their capacity as mothers and wives.